Pengaruh E-Wom, Citra Destinasi dan Fasilitas terhadap Kepuasan Wisatawan di Kebun Raya Purwodadi - Vania Nurfadillah Putri; Nanny Roedjinandari; Andini Risfandini (Studi Ilmu Manajemen dan Organisasi, 2023)
Purpose: The aim of this research is to analyze the influence of e-WOM, Image, and Facilities in tourism destinations because those three variables are connected and are used to build visitors’ perception of a tourist destination and serve as some of the determinant factors of tourist satisfaction. Methodology: This research is using a quantitative approach by distributing survey questionnaires to 120 respondents. However, the fully filled-up questionnaire is only 100. Results: The result of the survey questionnaire is analyzed using SPSS 25 software with descriptive statistics and regression analysis. In this research, e-WOM is not influencing the satisfaction of visitors to Purwodadi Botanical Garden. However, images and facilities are influencing the visitors' satisfaction. All three variables are simultaneously influencing the visitor satisfaction of Purwodadi Botanical Garden so the management has to improve all those aspects. Limitation: This research has limitation because it is only investigating the influence of three variables to visitor satisfaction namely: e-WOM, image, and facilities. Other researchers are expected to study the influence of other variables to visitor satisfaction. Contributions: This research is filling up the gap of research on visitor satisfaction based on the influence of e-WOM, image, and facilities in Purwodadi Botanical Garden. Until this research is conducted, there are no other researcher conducting the research with the same variables on visitor satisfaction in Purwodadi Botanical Garden. The result of this research is expected to give insight to Purwodadi Botanical Garden to improve on visitor satisfaction.